PENERAPAN MEDIA ELEKTRONIK PADA PEMBELAJARAN BAHASA ARAB - Luluk Humairo Pimada; Muhammad Afif Amrulloh (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2020)
Electronic media is currently chosen as one of the solutions to be able to carry out educational activities in the midst of the 19th epidemic sweeping the world; even this application is also carried out for learning Arabic at MTs. level. This study aims to determine the application of electronic media in Arabic language learning, and identify obstacles faced by the students of MTs. Normal Islam Samarinda. The subject of this research is students, the data collection obtained through research instruments in the form of observation, interview, and documentation. Then the analysis of this study using the Miles and Huberman method through the process of data collection, data reduction, and drawing conclusion. The results of this study are the types of electronic media used are smartphones using learning application from social media in the form of whatsapp, google form, and google classroom. Then the obstacles faced internally are students learning styles and varied language skills, and learning motivation. While externally the obstacles come from the lack facilities, the environment that does not support, the cost of spending to support education, and extra time and energy.